REPRESENTATIVE SPEECH ACTS PERFORMEDBY THE DEBATERS IN AN ENGLISH DEBATE COMPETITION - Orin, Karlinda; Issy, Yuliasri (English Education Journal, 2016)
This study aims to analyze the types of representative speech acts performed by the debaters, the opponentsâ responses to representative speech acts in debate and the contribution of the representative speech acts to the development of argument in debate.This study used spoken discourse analysis especially speech act theory proposed by Schifrin (1994) for data analysis. The object of this study is English debate performed by the debaters. The result of this study shows that there are twelve types of representative speech acts in the debate (Searle and Vanderveken, 1985). The analysis on the opponentsâ response result shows that the highest opponents respond is âarguingâ acts than other acts. It meant that the debaters try to embrace and persuade the hearers so the hearers can comprehend and believe speakersâ feelings. The last, the representative speech acts to the development of argument in debate shows that the highest frequency distribution of representative speech acts is explaining 46.1 %. It is followed by exemplifying 19.4% and tie-back 18.1%. The small frequency distribution of representative speech acts in argumentsâ structure is labeling 16.3%. Thus, the speaker of the affirmative team successfully exploits the favorable contexts of their speech to persuade the hearers.